Sunlit Uplands: The Genius of the NICE Reference Case - Paul C Langley (University of Minnesota Libraries Publishing, 2016)
The NICE reference case has received widespread acceptance in health technology assessment. The lifetime cost-per-QALY model and constructed claims for product impact have been widely emulated in country-specific guidelines for formulary submission as well as in publications in the leading health technology journals. Unfortunately, from the perspective of the standards of normal science, adherence to the reference case standard means that the claims made are typically non-evaluable. They have to be taken at face value. They may suggest potential evaluable hypotheses for clinical and cost-effectiveness claims, but there is no requirement in the reference case for claims to be put in an evaluable form and for manufacturers to suggest possible protocols for product impact assessment. This is not an acceptable situation. Absent the standards for falsification and replication, which are at the core of the scientific method, we have no idea whether the claims accepted by NICE are right or even if they are wrong. If we accept the reference case paradigm should we conclude that the sunlit uplands of formulary decisions based on non-evaluable simulated claims for cost-effectiveness has been reached? Have we rejected natural selection in favor of intelligent design? Conflict of Interest None Type: Commentary